2013
DOI: 10.1634/theoncologist.2012-0261
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Therapy With Zoledronic Acid in Patients With Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: Background. The purpose of the study was to estimate the impact on survival and fracture rates of the use of zoledronic acid versus no use (or delayed use) in the adjuvant treatment of patients with early-stage (stages I-III) breast cancer. Materials and Methods. We performed a systematic review and meta-analysis of randomized clinical trials. Trials were located through PubMed, ISI, Cochrane Library, and major cancer scientific meeting searches. All trials that randomized patients with primary breast cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 44 publications
2
51
0
5
Order By: Relevance
“…In a comprehensive meta-analysis of 15 randomized clinical trials on adjuvant therapy for breast cancer patients with zoledronate, the authors identified a significant overall survival benefit with zoledronate treatment, in agreement with one smaller meta-analysis [2] but not another [3] conducted earlier. These new findings support the call for zoledronate to be considered as a new standard of care in adjuvant breast cancer therapy [4].The dilemma remains that the biological mechanism underlying the antitumor role of zoledronate is unclear, as Valachis et al correctly highlight [1]. The clinical benefit may in fact stem, at least in part, from the activity of zoledronate on the patient's immune system by specifically stimulating V␥9/V␦2 T cells, which compose 0.5%-5% of circulating T cells in healthy adults [5].…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…In a comprehensive meta-analysis of 15 randomized clinical trials on adjuvant therapy for breast cancer patients with zoledronate, the authors identified a significant overall survival benefit with zoledronate treatment, in agreement with one smaller meta-analysis [2] but not another [3] conducted earlier. These new findings support the call for zoledronate to be considered as a new standard of care in adjuvant breast cancer therapy [4].The dilemma remains that the biological mechanism underlying the antitumor role of zoledronate is unclear, as Valachis et al correctly highlight [1]. The clinical benefit may in fact stem, at least in part, from the activity of zoledronate on the patient's immune system by specifically stimulating V␥9/V␦2 T cells, which compose 0.5%-5% of circulating T cells in healthy adults [5].…”
mentioning
confidence: 60%
“…
We read with great interest the article by Valachis et al [1], published in The Oncologist. In a comprehensive meta-analysis of 15 randomized clinical trials on adjuvant therapy for breast cancer patients with zoledronate, the authors identified a significant overall survival benefit with zoledronate treatment, in agreement with one smaller meta-analysis [2] but not another [3] conducted earlier.
…”
mentioning
confidence: 99%
“…The only two phase iii trials that considered cancer-specific primary endpoints and compared adjuvant therapy with and without za (abcsg-12 and azure) independently suggested that adjuvant za improves breast cancer outcomes in patients with low circulating estrogen levels secondary to induced or natural menopause 13,14 . Meta-analyses of adjuvant za and adjuvant bisphosphonate trials as a whole appear to confirm the benefit in that subgroup of patients 6,[15][16][17] .…”
Section: Introductionmentioning
confidence: 86%
“…Many prospective studies have been performed and several systematic reviews and meta-analyses have been published [14,15,16]. Hypotheses from early BP trials include that antitumor effects are mainly due to a reduction in bone metastases and that distant recurrence is predominantly reduced as compared to local or contralateral recurrence.…”
Section: Bps As Anticancer Agentsmentioning
confidence: 99%
“…In the first systematic review by Mauri et al in 2010 [14], ZA was not associated with a significant reduction in bone metastases or death. In the latest peer-reviewed meta-analysis by Valachis et al from 2013 [16] including 15 eligible trials, a significant improvement for overall survival and fracture rates but not for disease-free survival or incidence of bone metastasis was shown for the overall study population (table 1), a finding that cannot be interpreted easily.…”
Section: Bps As Anticancer Agentsmentioning
confidence: 99%